Deficiency of the RNA-binding protein ELAVL1/HuR leads to the failure of endogenous and exogenous neuroprotection of retinal ganglion cells - Pacwa, Anna; Machowicz, Joanna; Akhtar, Saeed; Rodak, Piotr; Liu, Xiaonan; Pietrucha-Dutczak, Marita; Lewin-Kowalik, Joanna; Amadio, Marialaura; Smedowski, Adrian (Frontiers in Cellular Neuroscience, 2023)
Hu/ELAV-like 1 (ELAVL1)/HuR is a keystone regulator of gene expression at the posttranscriptional level, with roles in the stress response and maintaining homeostasis. The aims of this study were to evaluate the effect of hur silencing on survival and oxidative stress markers in B-35 cells exposed to temperature and excitotoxic insults, on the age-related degeneration of retinal ganglion cells (RGCs), which potentially describes the efficiency of endogenous neuroprotection mechanisms, and to assess the exogenous neuroprotective capacity of hur-silenced RGCs in a rat glaucoma model using electrophysiological and histological methods. Silencing of hur induced apoptosis and increased oxidative stress markers in B-35 cells. Additionally, shRNA treatment impaired the cellular stress response to temperature and excitotoxic insults. In vivo, RGC count was decreased by 39% in shRNA-HuR group 6 months after injection, when compared to shRNA scramble control group. In neuroprotection study, the average loss of RGCs was 35% in animals with glaucoma treated with metallothionein and shRNA-HuR and 11.4% in animals with glaucoma treated with metallothionein and the scramble control shRNA. An alteration in HuR cellular content resulted in diminished photopic negative responses in the electroretinogram. Based on our findings, we conclude that HuR might be an essential factor for the survival and efficient neuroprotection of RGCs and that the induced alteration in the HuR content accelerates both, the age-related and glaucoma-induced deceleration in RGC number and function, further confirming the key role of HuR in maintaining cellular homeostasis and its possible involvement in the pathogenesis of glaucoma.